Bishop John Hacket and his teaching on sanctity and secularity - Knox, R. Buick - (Studies in church history, 1973)
John hacket was the son of a Scot who had prospered in business in London and had become a burgess in the city of Westminster. John was born in 1592 and passed through Westminister school to Trinity college, Cambridge, of which he became a fellow in 1616. His later episcopal eminence is attested in the full-scale portrait which adorns the walls of the Wren library in the college and in the bishop’s hostel which was founded in the college by his generosity in 1670. He was ordained by bishop King of London on 20 December 1618. By then he had already come under the influence of John Williams, a fellow of the neighbouring St John’s college, whose ability and charm were soon to take him to the deanery of Westminster, the bishopric of Lincoln, and the high office of lord keeper of the great seal. He took Hacket into his household as his chaplain and furthered his career by introducing him to the court where he became a royal chaplain. Williams also assisted his rise in the ecclesiastical firmament by appointing him to a prebend in Lincoln cathedral and then to the archdeaconry of Bedford, and by influencing the king to secure his appointment to the rectory of St Andrew’s, Holborn, and to the rectory of Cheam. His Holborn pulpit proved to be a position of great influence and he drew a large congregation, especially from the upper classes of society. His prestige among the clergy of London was so high that he was chosen by them in 1634 to be the second president of Sion college, an institution founded in 1633 as a centre where the city clergy could meet and study.